Oomycetes found in wild and cultivated areas of Vietnam - Pfeufer, Emily E.; Groben, Glen; Harrison, Lindsay; Quang Thu, Pham; Widmer, Timothy; Puig, Alina S. (Frontiers in Microbiology, 2026)
To determine the diversity of oomycetes in Vietnam, particularly in the presumed center of origin of most Phytophthora taxa, isolates were collected from rivers, agricultural soils, and forested areas. Species identification was performed using sequences from the internal transcribed spacer (ITS) and cytochrome 2 oxidase (cox2) regions of the genome. Of the 245 isolates included in this study, the majority (66.5%) were identified as Phytopythium spp., followed by Phytophthora spp. (31%) and Pythium spp. (2.4%). The most prevalent species were Phytopythium vexans and Phytophthora cinnamomi, accounting for 51.8 and 24.5%, respectively, of all isolates obtained. A total of 17 isolates were identified as belonging to multiple undescribed species. From agricultural soils, only one isolate each of Phytophthora and Pythium was obtained, with the remaining 93% belonging to the genus Phytopythium. This study shows that natural and agricultural areas in Vietnam harbor a wide diversity of oomycetes, including several undescribed species. The identification of oomycete species in a center of origin will help identify potential emerging pathogens that can become a threat to U.S. agriculture.